Further studies in the making of the early Hebrew book - Heller, Marvin J. (The Brill Reference Library of Judaism, 2013)
Further Studies in the Making of the Early Hebrew Book contains essays on aspects of the early Hebrew book most often treated in a cursory manner if addressed at all. The largest section of the volume is concerned with the makers and places of Hebrew books, mainly addressing book-makers poorly remembered or controversial and print-shops that issued a small number of books in a brief period of time. The section on varia addresses aspects of the book trade such as small books, incomplete books published as a prospectus, competing simultaneous editions, and errors and variations in books. Two smaller sections deal with book arts such as incunabula frames and pressmarks; variations between medieval and current Sephardic Haggadot.